Fruits basket. 5 - Takaya, Natsuki, 1973- (Fruits Basket Collectors Edition, 2016)
"As summer vacation inches closer, Tohru spends her days in anxious anticipation, Yuki meets two mysterious new student council members ... and Uo-chan is in love?! Who is the object of her affection?! Once summer break is in full swing, Tohru and the others take a trip to the Sohma family cottage at Momiji's invitation. Even though they're enjoying summer activities like swimming in the ocean and catching stag beetles, Yuki and Tohru have an ominous premonition! Meanwhile, Shigure pays a visit to the main house, where he makes a proposal to Akito?!"--Cover flap.